Sketch: From Design To Delivery (Taxi Beat Greece) - Mouzouropoulos, Theseas (My University, 2026)
Sketch: From Design To Delivery, , Athens, Greece This workshop was held by Theo Tsongidis (Taxi Beat Greece) and it was focused on the design processes as well as the technical aspects of user interface and experience design (UI/UX)